Peritoneal lavage during laparoscopic appendectomy for complex appendicitis is associated with increased post-operative morbidity - Darren Puttock; Vikrant Kumbhar; Haitham Dagash; Nitin Patwardhan (Wolters Kluwer Medknow Publications, 2022)
Aim: Appendicitis is one of the most common paediatric surgical pathologies seen by paediatric surgeons worldwide. Laparoscopic appendectomy is undertaken for all cases of appendicitis in our institute. Intraperitoneal lavage following appendectomy is the conventional way of managing complicated appendicitis; however, some surgeons debate the efficacy of this practice. The aim of this study was to compare outcomes of intraperitoneal lavage versus suction only in children with complicated appendicitis. Methods: Data were collected retrospectively between January 2018 and January 2019. All patients undergoing laparoscopic appendectomy for complex appendicitis were included and divided into two groups, patients who had suction only and those who had lavage and suction. Outcome parameters studied were the length of stay (LOS), number of temperature spikes > 37.7 (TS), operative times (OT) and readmission for intra-abdominal collections. Comparison between the two groups was performed using two sample t-test with unequal variance, significance was set at P < 0.05. Results: A total of 115 patients were included (lavage n = 52, Suction n = 63). The LOS (P = 0.0054), TS (0.0109), OT (P < 0.0001) were significantly higher in the lavage group compared to the suction-only group. Overall rates of readmission were similar between groups, however, readmission for the confirmed intra-abdominal collection was more common in the lavage group. Conclusion: Based on our study, it appears that there is no advantage in performing an intraperitoneal lavage for complex appendicitis. It resulted in a prolonged stay, more post-operative TS and longer operative duration. The likelihood of being readmitted with an intra-abdominal collection following a lavage was higher compared to suction only.